2022
DOI: 10.1017/dce.2022.7
|View full text |Cite
|
Sign up to set email alerts
|

Principal component density estimation for scenario generation using normalizing flows

Abstract: Neural networks-based learning of the distribution of non-dispatchable renewable electricity generation from sources, such as photovoltaics (PV) and wind as well as load demands, has recently gained attention. Normalizing flow density models are particularly well suited for this task due to the training through direct log-likelihood maximization. However, research from the field of image generation has shown that standard normalizing flows can only learn smeared-out versions of manifold distributions. Previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In Cramer et al (2022b), we showed that normalizing flows sample uncharacteristically noisy scenarios when applied to sample for the distributions of renewable electricity time series, due to their inherent lower-dimensional manifold structure. To address the issue, we proposed dimensionality reduction based on the principal component analysis (PCA).…”
Section: Conditional Density Estimation Using Normalizing Flowsmentioning
confidence: 99%
See 4 more Smart Citations
“…In Cramer et al (2022b), we showed that normalizing flows sample uncharacteristically noisy scenarios when applied to sample for the distributions of renewable electricity time series, due to their inherent lower-dimensional manifold structure. To address the issue, we proposed dimensionality reduction based on the principal component analysis (PCA).…”
Section: Conditional Density Estimation Using Normalizing Flowsmentioning
confidence: 99%
“…The conditional input vectors y are not affected by the PCA. For more information on the effects of manifolds we refer to Brehmer and Cranmer (2020), Behrmann et al (2021), andCramer et al (2022b).…”
Section: Conditional Density Estimation Using Normalizing Flowsmentioning
confidence: 99%
See 3 more Smart Citations